APOPTOSIS STUDY OF INDONESIAN AVIAN INFLUENZA VIRUS SUBTYPE H5N1 IN MADIN-DARBY CANINE KIDNEY CELLS - NLP Indi Dharmayanti; Dwi Rillah Ukhti; Farida Syamsiah; Risza Hartawan (Jurnal Kedokteran Hewan, 2017)
This study aimed to determine the ability of highly pathogenic avian influenza virus (HPAI) virus subtype H5N1 originated from Indonesia to induce apoptosis in Madin-Darby Canine Kidney (MDCK) cells. Three HPAI virus subtype H5N1 isolates with different genetic characteristic namely A/Bird/Bali1/2011, A/Chicken/East Java/BwiI2/2010 and A/Chicken/West Java/1074/2003, were cultured in MDCK cells. Apoptosis was identified by deoxyribonucleic acid (DNA) fragmentation of infected MDCK cells using Apoptotic DNA Ladder Kit. The results showed that all three HPAI virus isolates used in this study did not able to induce apoptosis in the MDCK cells within 5 to 72 hours post infection.